Dialogi polityczne brytyjskiego kina. Wizerunki Amerykanów i Niemców w kinie angielskim okresu II wojny światowej - Kazana, Bartosz (Er(r)go. Teoria - Literatura - Kultura, 2013)
Bartosz Kazana Political Dialogues of British Cinema. Images of Americans and Germans in the English Film of the WW II Period. Films from the so called British War Collection, produced in England between 1941 and 1945 present a wide spectrum of propagandist cinema: from information and educational films to motions pictures warming up to fight or shaping political moods of the society. Among those one could find films supposed to ease the tense relations between the English and American soldiers stationed on British Islands. In most cases those films depicted a conventionalized image of both nations’ representatives by referring to obvious cultural and customary differences. However, some eminent productions used the expressive topic as a pretext for artistic experimentation. For obvious reasons during the war the Germans were supporting characters in numerous films. Those movies constitute particularly interesting research material since they contain complex profiles of such characters and are not always limited to depicting a travesty or unambiguous condemnation. More ambitious filmmakers, such as Carol Reed, and, more importantly Michael Powell together with Emeric Pressbugrger, not only problematize various aspects of war but also complicate the Germans’ psychological descriptions by drawing a clear dividing line between a German and a Nazi. The article recalls most representative films for both groups and, by comparing them, aims at demonstrating their ideological and artistic diversity.